Towards Energy Analysis and Efficiency for Sustainable Buildings - Deshinta A. Dewi; Fathoni Usman; Fadly Fadly; Tri B. Kurniawan (Emerging Science Journal, 2023)
Energy analysis that leads to energy efficiency becomes one of the most important factors in the building design process, especially considering the current energy crisis and the effects of global warming. Building designers greatly benefited from the review and analysis to optimize energy usage for the building in the design stage. While the current design approach is mostly done manually, this paper presents the automated version using the developed BIM plugin. It eases the designer’s choice of alternative plans that yield an effectively designed building. The development of energy analysis in the application aims to promote energy efficiency by calculating the energy consumption estimation based on energy codes MS2680 and MS1525. This application is improved by a simulation that uses the Building Information Modeling (BIM) platform and extracts the necessary parameters from the BIM model with the aid of the created plugins. This study measured energy consumption and efficiency using the two primary parameters of Overall Thermal Transfer Value (OTTV) and Roof Thermal Transfer Value (RTTV). According to the results, OTTV reaches 42.72% and RTTV reaches 8.02%, both of which respectively meet Malaysian Energy Code limits of less than 50% and 25%. Doi: 10.28991/ESJ-2023-07-06-022 Full Text: PDF